2021
DOI: 10.2147/nsa.s294412
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide and Stabilized Ortho-Silicic Acid as Modifiers of Amnion and Burn Affected Skin: A Comparative Study

Abstract: Introduction Oxidative tissue damage caused by reactive oxygen species results in a significant decrease in the total antioxidant capacity of the biological system. The aim of this interdisciplinary study was to answer the question of whether active antioxidants modify, at a molecular and supramolecular level, the tissue of pathological amnion and the necrotic eschar degraded in thermal burn. Methods A Nicolet 6700 Fourier-transform spectrophotometer with OMNIC software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…The outstanding physicochemical characteristics, antimicrobial activity, and biocompatibility of graphene, its derivatives, and nanocomposites make them promising candidates for a large variety of antimicrobial applications, presented in Figure 2. They could be summarized as follows [54][55][56]: support to disperse and stabilize various nanomaterials, such as metals, metal oxides, and polymers with high antibacterial efficiency due to the synergistic effect [55]; antibacterial agents for treatment of multidrug-resistant bacterial infections [34,57]; drug-delivery systems (based on the two-dimensional planar structure, large surface area, chemical and mechanical stability, and good biocompatibility) [34,58]; coatings for medical devices, membranes, and others, due to bread-spectrum antimicrobial activity [59][60][61][62][63][64]; creation of smart material surfaces (graphene materials with controllable wettability) [65]; biosensing and bioimaging (due to the ability to conjugate biomolecules and fluorescent dyes) [54], photothermal therapy (because of the high nearinfrared absorbance of the graphene) and gene therapy [54]; dentistry adhesives and dentin coatings [30,45]; endodontic (irrigants and intracanal medicaments; root canal disinfection) and the regenerative endodontics (support of bioactive molecules and enhancing the scaffold properties [66]; wound dressing and healing [33,40,[67][68][69][70][71]; sewage systems [72]; tissue repair, tissue and organ engineering (made possible by the ability of Gr materials to stimulate the growth of eukaryotic cells and to inhibit the microbial cells attachment and growth; 3D printing of 2D graphene to fabricate 3D structure for bone tissue scaffolds) [54]; antibacterial packaging [73]; water purification membranes…”
Section: Potential Applications Of Graphene Nanomaterialsmentioning
confidence: 99%
“…The outstanding physicochemical characteristics, antimicrobial activity, and biocompatibility of graphene, its derivatives, and nanocomposites make them promising candidates for a large variety of antimicrobial applications, presented in Figure 2. They could be summarized as follows [54][55][56]: support to disperse and stabilize various nanomaterials, such as metals, metal oxides, and polymers with high antibacterial efficiency due to the synergistic effect [55]; antibacterial agents for treatment of multidrug-resistant bacterial infections [34,57]; drug-delivery systems (based on the two-dimensional planar structure, large surface area, chemical and mechanical stability, and good biocompatibility) [34,58]; coatings for medical devices, membranes, and others, due to bread-spectrum antimicrobial activity [59][60][61][62][63][64]; creation of smart material surfaces (graphene materials with controllable wettability) [65]; biosensing and bioimaging (due to the ability to conjugate biomolecules and fluorescent dyes) [54], photothermal therapy (because of the high nearinfrared absorbance of the graphene) and gene therapy [54]; dentistry adhesives and dentin coatings [30,45]; endodontic (irrigants and intracanal medicaments; root canal disinfection) and the regenerative endodontics (support of bioactive molecules and enhancing the scaffold properties [66]; wound dressing and healing [33,40,[67][68][69][70][71]; sewage systems [72]; tissue repair, tissue and organ engineering (made possible by the ability of Gr materials to stimulate the growth of eukaryotic cells and to inhibit the microbial cells attachment and growth; 3D printing of 2D graphene to fabricate 3D structure for bone tissue scaffolds) [54]; antibacterial packaging [73]; water purification membranes…”
Section: Potential Applications Of Graphene Nanomaterialsmentioning
confidence: 99%
“…Analysis of the AH1 SA and BH1 AA series revealed that the presence of SA causes flattening of the disulfide-bond area, whereas the incubation in AA resulted in a slight exposure of the 510 cm −1 (S-S gauche-gauche-gauche) and 528 cm −1 bands (S-S gauche-gauche-trans), as well as formation of the 564 cm −1 band (S-S trans-gauche-trans) (Figure 4). In thermogravimetric studies, 26 an increase in the stability of BS GO samples after incubation in GO solutions has been observed, which is confirmed by the presence of bands near 510 cm −1 for the gauche-gauche-gauche conformation of C-C-S-S-C-C, which are considered the most stable form of disulfide bonds. Incubation of samples of burn-damaged epidermis in GO solutions also results in changes in the FTR spectrum in the area of 520-562 cm −1 : S-S stretch trans and gauche conformers, 63 ie, separation of the S-S gauche-gauchetrans and 561 cm −1 (S-S trans-gauche-trans).…”
Section: Dovepressmentioning
confidence: 67%
“…However, in the case of hypotrophic amniotic samples, changes — as characteristic as for AA — in the broadly understood lipid area occur during the interaction of amniotic membranes with SA. 26 What is more, this paper has demonstrated that when using higher concentrations of antioxidants (7%, ie, 3.5 g AA for samples of BH1 AA; Figure 4A ) for incubation of amniotic samples, strengthening of the lipid band 1,754 cm −1 was observed, which indicates a surface effect. For lower concentrations of antioxidants (0.001 g for BS SA and BS AA samples), an aspect characteristic of SA, the so-called intermolecular exchange within the membrane, was revealed.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations